Kebijakan Indonesia dalam Kerja Sama Trans-ASEAN Gas Pipeline - , Arif Rahman Hakim; , Dr. Nur Rachmat Yuliantoro, MA (IR) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Towards the establishment of the ASEAN Community 2015, states of Southeast Asia have many challenges include from energy. The high interdepence on energy of outside the region such as oil, cause this region susceptible to the geopolitical situation in the Middle East. solve these To problems, ASEAN have established cooperation in the energy sector, such as the Trans ASEAN Gas Pipeline. TAGP formed because of the large natural gas reserves located in Southeast Asia that reach up to 227 trillion cubic feet and has great potential to replace the role of oil in industrial activities in Southeast Asia. This cooperation has participated by the ten countries of Southeast Asia, including Indonesia. setting Indonesia's participation in this cooperation is influenced by internal and external in the country. The Internal setting are the failure of a government program to increase the usage of natural gas in the country, the national economy after the crisis of 1998, and a low level of gas consumption in the country. While external factors are a change in the structure of the natural gas market in the world, changes in natural gas policy in East Asia including Japan and the emergence of ASEAN energy security policy as a condition of supporting the establishment of an ASEAN Community by 2015. many TAGP also offers a of benefits for Indonesia such as support programs to reduce the usage of oil, facilitate the delivery of gas to foreign countries, improving energy supply security support such as electricity, increasing national income, reducing the effects of environmental change, and easing the national gas project financing. Finally, in 2002 Indonesia decide to cooperation in the TAGP.